2004
DOI: 10.1080/09513590400004710
|View full text |Cite
|
Sign up to set email alerts
|

Gamete intra-Fallopian transfer or intrauterine insemination after controlled ovarian hyperstimulation for treatment of infertility due to endometriosis

Abstract: We compared the effectiveness of gamete intra-Fallopian transfer (GIFT) and intrauterine insemination (IUI) after controlled ovarian hyperstimulation (COH) in the treatment of infertility due to endometriosis. This was a retrospective study carried out at a tertiary teaching medical center. A total of 127 consecutive patients with endometriosis were treated with GIFT or IUI after COH between June 1990 and December 1998. Patients were divided into two groups. Group 1 (n = 97) included patients with stages 1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…In our study, approximately one-third of patients with advanced endometriosis were able to conceive within 2 years after operative laparoscopy as a result of spontaneous trials and/or IUI+COH. Other reports suggested similar results when IUI+COH was used after operative laparoscopy for early and advanced endometriosis [25][26][27]. Therefore, it could be offered for two to three cycles either immediately following surgery or after three to four failed cycles of spontaneous trials.…”
Section: Discussionsupporting
confidence: 50%
“…In our study, approximately one-third of patients with advanced endometriosis were able to conceive within 2 years after operative laparoscopy as a result of spontaneous trials and/or IUI+COH. Other reports suggested similar results when IUI+COH was used after operative laparoscopy for early and advanced endometriosis [25][26][27]. Therefore, it could be offered for two to three cycles either immediately following surgery or after three to four failed cycles of spontaneous trials.…”
Section: Discussionsupporting
confidence: 50%
“…Figures , , S3 and S4 report the results of the 29 individual studies included in the quantitative review that had compared Stage‐III/IV vs Stage‐I/II endometriosis.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 176 records were completely assessed for eligibility, of which 84 studies were excluded with reasons: 70 studies did not compare endometriosis vs control or Stage III/IV vs Stage I/II endometriosis undergoing ART; eight studies did not report any of the evaluated outcomes; five studies included participants reported in newer or larger studies; and one study included only women who achieved pregnancy. We included 92 studies in this review, of which 78 studies were included in the quantitative meta‐analysis: 21 for both comparisons; 49 only for the comparison ‘endometriosis vs control’; and eight only for the comparison ‘Stage III/IV vs Stage I/II endometriosis’. Fourteen studies were included only in the qualitative review: two studies for both comparisons…”
Section: Resultsmentioning
confidence: 99%
“…It was previously shown that the addition of a GnRH agonist down-regulation to the stimulation protocol of IUI improves the outcome (11). Using a GnRH agonist and hMG protocol, a previous report from our unit has shown that COH-IUI can be as effective as gamete intrafallopian transfer procedures in patients with early stages of endometriosis (10).…”
Section: Sakhel Comparison Between R-hcg and U-hcg Fertil Steril 2007mentioning
confidence: 96%
“…The use of GnRH agonist and, more recently, GnRH antagonist is an essential component of our stimulation protocol (10). It was previously shown that the addition of a GnRH agonist down-regulation to the stimulation protocol of IUI improves the outcome (11).…”
Section: Sakhel Comparison Between R-hcg and U-hcg Fertil Steril 2007mentioning
confidence: 99%